Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Keistiqomahan Shalat Fardhu Siswa SMA Negeri 2 Galing - Ashari; Arnadi; Sri Sunantri (CV Putra Publisher, 2023)
Prayer is a medium of communication between creatures and the creator. Prayer is a deterrent from evil and evil deeds. If you look at the current reality among teenagers, there have been a lot of negligence in many things. Therefore, it is necessary to have the habit of praying together at school so that good habits are embedded in teenagers from an early age. This study focused on the role of PAI teachers in disciplining the congregational prayer of students at SMAN 2 Galing Sambas with the following problems formulation: (1) the process of praying zuhur in congregation through the cooperation of teachers and parents of students, (2) the approach taken by PAI teachers in motivate students to pray zuhur in congregation, and (3) obstacles and obstacles for PAI teacher to improve the istiqomah of zuhur prayer in congregation. To achieve these objectives using a qualitative descriptive method, while the data collection used is observation, interviews, and documentation. The researcher uses descriptive analysis which aims to explain aspects that are relevant to the observed phenomena. The results showed that (1) The process of implementing the Zuhur prayer in congregation was carried out through the coordination of the principal, PAI teacher and parents of students. Coordination between the Principal and Islamic Religious Education Teacher and parents of students in improving the quality of congregational prayers at SMAN 2 Galing, Sambas Regency. This coordination is to discuss school programs and one of them is related to congregational prayers. The purpose of this coordination is to improve the quality of student prayer in congregation, (2) The approach taken by PAI teacher in motivating students to pray Zuhur in congregation at SMAN 2 Galing, Sambas Regency is still not optimal. The approach taken by PAI teacher is a religious approach through tausiyah activities, lectures, cults and giving advice to students. Then the individual approach focuses more on the guidance and practice of reading prayers. In addition, the prayer control book is used in an effort to improve the discipline of students praying in congregation. Finally, a group approach that leads to group guidance for students who have not been able to memorize prayer readings, and (3) Obstacles and obstacles for PAI teachers to improve the istiqomah of Zuhur prayer in congregation at SMAN 2 Galing, Sambas Regency, including internal and external obstacles and barriers. external. Internally, the obstacles and obstacles are the lack of awareness of some students to pray in congregation. Then, externally, the obstacles and constraints include the incomplete facilities for ablution facilities which are limited in the number of water faucets. In addition, many students do not bring a mukenah with the excuse of forgetting. Another obstacle that arises is the lack of involvement of other teachers in controlling, checking and reprimanding students who do not pray in congregation.